Is ESG Companies' Performance Influenced by Ownership Structure? Evidence in ASEAN - Kurniawan, Ivana; Rokhim, Rofikoh (International Journal Labs, 2023)
Background: According to studies on sustainability dimensions – environmental, social, and governance (ESG) – companies that effectively address the stakeholders’ ESG expectations are likely to outperform companies that poorly implement ESG principles. Studies show mixed results of the relationship between ESG and financial performance. Besides, ESG adoption in ASEAN countries is still in early stage compared with European countries or US region. Aim: The purpose of this paper is to investigate the relationship between Environmental, Social and Governance (ESG) performance and firm performance of ASEAN listed companies moderated by company ownership structure. Method: This paper selects publicly listed companies in ASEAN stock exchanges with data period of 2017-2021, a total of 607 companies samples with 1,309 data observations. Refinitiv Eikon ESG rating is adopted in this paper to measure ESG performance while ownership structure is measured in three aspects, which include ownership concentration, equity balances, and institutional investor shareholding. Findings: The research found that (1) ESG performance has negative and significant relation to both market-based and accounting-based firm performances, (2) ownership concentration has no significant moderating role on ESG – firm performance relationship, (3) equity balance is only significant in moderating ESG relationship to Tobin’s Q, meanwhile (4) institutional ownership is found statistically significant in moderating the ESG relationship to Tobin’s Q and ROE but not to ROA.